Mycobacterial Protein HbhA Binds Human Complement Component C3 - Mueller-Ortiz, Stacey L. (American Society for Microbiology, 2001)
Mycobacterium tuberculosis and Mycobacterium avium are facultative intracellular pathogens that are able to survive and replicate in mononuclear phagocytes. Human complement component C3 has previously been shown to mediate attachment and phagocytosis of these bacteria by mononuclear phagocytes. In this study, a C3 ligand affinity blot protocol was used to identify a 30-kDa C3-binding protein in M. tuberculosis and Mycobacterium smegmatis and a 31-kDa C3-binding protein in M. avium. The C3-binding proteins in M. tuberculosis and M. avium localized to the cell membrane fraction and partitioned to the detergent fraction during Triton X-114 phase partitioning. The C3-binding protein from M. tuberculosis was partially purified using a cation exchange column and was shown to bind concanavalin A. The N terminus and an internal fragment of the partially purified C3-binding protein were subjected to amino acid sequence analysis. The resulting amino acid sequences matched the M. tuberculosis heparin-binding hemagglutinin (HbhA) protein. Recombinant full-length HbhA and the C terminus of HbhA fused to maltose-binding protein, but not recombinant HbhA lacking the C-terminal region, bound human C3. Recombinant full-length HbhA coated on polystyrene beads, was found to enhance the adherence and/or phagocytosis of the coated beads to J774.A1 cells in both the presence and absence of human serum. The presence of complement-sufficient serum increased the adherence of the HbhA-coated beads to the J774.A1 cells in a C3-dependent manner. If HbhA within the bacterial cell membrane functions similarly to isolated HbhA, this protein may enhance the adherence and phagocytosis of M. tuberculosis and M. avium to mononuclear phagocytes through the binding of C3 and interaction with C3 receptors on mononuclear phagocytes.